Development and preliminary mechanistic analysis of compound effervescent hepatoprotective granules - Liu, Xinyao; Wang, Ruru; Li, Yumeng; Zhang, Jing; Li, Jingjing; Li, Shuangping; Ye, Qingping; Cao, Renting; Wang, Wen; Luo, Wenhui; Beng, Shujuan; Duan, Xianchun; et al. (Frontiers in Nutrition, 2025)
BackgroundThe causes of acute liver injury (ALI) are complex and diverse, including alcohol, drugs, infections, and toxic substances, and it has become a major global health issue. Traditional Chinese medicine (TCM), with advantages such as broad-spectrum biological activity, low toxicity, and minimal side effects, has been widely used in drug research and development as well as disease management. Some TCMs have shown significant efficacy in treating ALI: Ganoderma lucidum polysaccharides, monoterpene glycosides from Paeonia lactiflora, glycyrrhizic acid saponins, and flavonoids all exhibit liver-protective effects; however, the protective effects of their compound preparations on liver injury remain unclear.MethodsThe study optimized the water extraction process using orthogonal experiments with AHP-entropy weight scoring. The preparation process was verified by single-factor experiments, Plackeett–Burman and Box–Bohnken tests. The mechanism of action was validated using network pharmacology methods and a CCl4-induced acute liver injury animal model.ResultsThe developed extraction and granule formation processes were reliable after validation. The contents of active components in CEHG determined by HPLC were as follows: albiflorin 1.26%, paeoniflorin 5.42%, liquiritin 0.43%, glycyrrhizic acid 1.30%, and ganoderic acid A 0.14%, with batch-to-batch variation coefficients (RSD) of 1.66%, 0.87%, 2.32%, 1.60%, and 4.03%, respectively. The dry extract ratio was 18.23% with an RSD of 2.11%. Network pharmacology revealed that CEHG improved liver injury by regulating the HIF-1, p53, and FoxO signaling pathways. Animal experiments indicated that CEHG granules reduce liver function-related aspartate transaminase (AST), alanine transaminase (ALT), total cholesterol (TC), triglyceride (TG), total bilirubin (TBIL), and LDH levels, decrease the levels of inflammatory factors IL-6, IL-1β, and TNF-α and of oxidative stress-related MDA and ROS, and down-regulated the mRNA and protein levels of P53, Bax, and HIF-1α in rats with liver injury. Meanwhile, CEHG improved liver function-related Total Protein (TP), raised the levels of oxidative stress-related SOD, GSH-Px, and GSH, and up-regulated mRNA and protein expression of Bcl-2.ConclusionThis study successfully optimized the extraction and granule-formation of CEHG and revealed its hepatoprotective mechanism through network pharmacology and animal studies, providing scientific evidence supporting the further development and clinical use of CEHG.